The Politics of Digital Pharmacology Exploring the Craft of Collective Care - Heidenreich, Felix (Edition Politik, 2022)
Digitization is transforming our world economically, culturally, and psychologically. The influx of new forms of communication, networking, and business opportunities, as well as new types of distraction, self-observation, and control into our societies represents an epochal challenge. Following Bernard Stiegler's concept of pharmacology, Felix Heidenreich and Florian Weber-Stein propose to view these new forms as digital pharmaka. Properly dosed, they can enable new self-relationships and forms of sociality; in the case of overdose, however, there is a risk of intoxication. In this essay, Felix Heidenreich, Florian Weber-Stein, and, in a detailed interview, Bernard Stiegler analyze this complex change in our world and develop new skills to use digital pharmaka.